The Impact of Innovation on Business Development. The Example of Moderate Innovators and the Visegrad Group Countries - Jabłońska, Małgorzata (Comparative Economic Research. Central and Eastern Europe, 2024)
The paper analyzes the relationship between innovation dimensions, according to the European Innovation Scoreboard, and the entrepreneurship rate in a group of moderate innovator countries. Using the Pearson linear correlation, the author conducted a data analysis based on an empirical study using open data from the Summary Innovation Index – European Innovation Scoreboard (SII‑EIS) and Eurostat for 2013–2019. This period covers the moment when all the countries of the Visegrad Group (i.e., the Czech Republic, Hungary, Poland, and Slovakia – the V4) were classified into the same innovation group according to EIS. However, due to the volume limitations of the article, it was decided that Moderate Innovators from 2019 would be included in the comparative analysis, i.e., when the V4 were last collectively classified as Moderate Innovators. The results of the research positively verify the initial research hypothesis that the EIS indicators show a different strength of relationships with the entrepreneurship rate in the V4 and among other economies classified as Moderate Innovators (according to SII–2020). The variables that describe the quantity and quality of entrepreneurs’ innovations strongly and positively impact the V4 countries’ entrepreneurship rate. In other countries, the variables derived from the investment attractiveness of economies show a significant and positive correlation with the entrepreneurship rate. Based on the analysis of the results, it can be concluded that there is a strong positive correlation between the entrepreneurship rate and the total innovation index, which is compiled each year based on a set of variables for the European Union countries. The study showed that the entrepreneurship rate in these countries is strongly impacted by indicators representing the following groups: Innovators (small and medium‑sized enterprises (SMEs) with product or process innovations; SMEs with marketing or organizational innovations and SMEs innovating in‑house), Attractive research systems (international scientific co‑publications), Finance and support (Venture capital expenditures), Firm investments (Enterprises that provide training to develop or upgrade their personnel’s ICT skills), and Linkages (Innovative SMEs that collaborate with others). The impact of these factors on the development of entrepreneurship in the V4 means that pro‑innovative activities undertaken in operating enterprises strongly correlate with deciding to start one’s own business. Therefore, it can be concluded that entrepreneurship in these countries has an entirely different development basis than in other countries that are Moderate Innovators, where the factors mentioned above were irrelevant.